Stem Cell Renewal and Cell-Cell Communication Methods and Protocols - Turksen, Kursad; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume examines cell-cell interactions and stem cell renewal, two topics that are now inexorably linked as science strives to understand the stem cell niche and its function. Gathering a number of representative protocols, this detailed collection promises to provide readers with approaches for studying these complimentary aspects of stem cells. Written for the highly successful Methods in Molecular Biology series, chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Practical and reliable, Stem Cell Renewal and Cell-Cell Communication: Methods and Protocols will aid researchers in using these methods to advance their own studies.
Laboratory Control and Basic Culture Protocols for Stem Cell Self-Renewal -- Advanced Fixation for Transmission Electron Microscopy Unveils Special Extracellular Matrix Within the Renal Stem/Progenitor Cell Niche -- Multiplex Immunoassays for Quantification of Cytokines, Growth Factors and Other Proteins in Stem Cell Communication -- Porous Membrane Culture Method for Expansion of Human Pluripotent Stem Cells -- Tuning Differentiation Signals for Efficient Propagation and In Vitro Validation of Rat Embryonic Stem Cell Cultures -- Generation, Expansion and Differentiation of Human Pluripotent Stem Cell (hPSC) Derived Neural Progenitor Cells (NPCs) -- Isolation, Long-Term Expansion, and Differentiation of Murine Neural Stem Cells -- Generation, Expansion, and Differentiation of Cardiovascular Progenitor Cells from Human Pluripotent Stem Cells -- A Practical Guide for the Isolation and Maintenance of Stem Cells from Tendon -- A Human Colonic Crypt Culture System to Study Regulation of Stem Cell-Driven Tissue Renewal and Physiological Function -- Ca2+ Handling in Mouse Embryonic Stem Cell Derived Cardiomyocytes -- Potential Application of Extracellular Vesicles of Human Adipose Tissue-Derived Mesenchymal Stem Cells in Alzheimer’s Disease Therapeutics -- Application of Fluid Mechanical Force to Embryonic Sources of Hemogenic Endothelium and Hematopoietic Stem Cells -- Electrophysiological Recordings from Neuroepithelial Stem Cells -- In Vivo Stem Cell Transplantation Using Reduced Cell Numbers.
Keywords: Cell biology; Cell Biology